Global design and local materialization : 15th International Conference, CAAD Futures 2013, Shanghai, China, July 3-5, 2013. Proceedings - Sun, Chengyu; Zhang, Jianlong (Communications in Computer and Information Science, 2013)
This book constitutes the refereed proceedings of the 15th International Conference on Computer-Aided Architectural Design Futures, CAAD Futures 2013, held in Shanghai, China, in July 2013. The 35 revised full papers presented were carefully reviewed and selected from 78 submissions. The papers are organized in topical sections on digital aids to design creativity, concepts, and strategies; digital fabrication and local materialization; human-computer interaction, user participation, and collaborative design; modeling and simulation; shape and form studies.